Short-term multicomponent exercise training improves executive function in postmenopausal women. - Dani Rahmat Ramadhana; Rizki Prayuda Putra; Michelle Abigail Sibarani; Sulistiawati Sulistiawati; Dewi Ratna Sari; Purwo Sri Rejeki; Lilik Herawati; Raden Argarini (PLoS ONE, 2024)
Declined cognitive function is commonly complained during the menopausal transition and continues afterward. Combining different exercises potentially leads to greater improvements in cognitive function, however, evidence of the benefits that accrue with multicomponent exercise training, specifically for postmenopausal women is limited. Therefore, this study aimed to investigate the effects of short-term multicomponent exercise training programs on executive function in postmenopausal women. Thirty women (59.8 ± 5.2 years), who were at least 12 months post menopause were allocated into a control (CON) group and an exercise (EX) training group. The EX group underwent a 2-week (five times/week) multicomponent exercise program comprising aerobic, strength, flexibility, and balance exercises for 40-60 min. Executive function was assessed by using the Stroop test and global cognitive function was assessed using the Mini-Mental State Examination (MMSE) at baseline (pre) and after 2 weeks (post) of exercise. The EX group showed improved performance in the Stroop test, with faster inhibition reaction time (ES (g) = 0.76; p = 0.039) and fewer errors across all tasks (color naming: g = 0.8, p = 0.032; word reading: g = 0.88, p = 0.019; inhibition: g = 0.99, p = 0.009; switching: g = 0.93, p = 0.012) following exercise intervention. Additionally, statistical analysis of the MMSE score showed a significant improvement (g = 1.27; p = 0.001). In conclusion, our findings suggest that a short-term multicomponent exercise program improves selective tasks of executive function in postmenopausal women along with global cognitive function. Trial registration ISRCTN13086152.